Experimental LoRa Network Power Consumption Model Using Multi-Hops - Alexander, Ulanov; Bolshakov, Ivan; Voskov, Leonid; Rolich, Alexey (2022 Moscow Workshop on Electronic and Networking Technologies (MWENT), 2022)
The article describes the study of data transmission methods in heterogeneous networks using LoRa relay and NB-IoT gateway for use in an underdeveloped or absent Internet network infrastructure. The analysis of the subject area is carried out, a multistage architecture of a heterogeneous network of the Internet of Things is proposed, using repeaters and a gateway to collect remote data. A method and a calculation model of energy consumption for the transmission of collected data using repeaters is proposed, which makes it possible to increase the energy efficiency of data transmission from end devices using autonomous powersources. A prototype of a data acquisition system withretransmission has been developed, which confirms the theoretical calculations. The practical value lies in increasing thebattery life and expanding the network coverage area.